2023
DOI: 10.48048/tis.2023.4181
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Organic Additives on Asymbiotic Seed Germination of Dendrobium cruentum Rchb. f. for In Vitro Micropropagation

Abstract: Dendrobium cruentum Rchb. f., a commercial orchid in Thailand, faces the risk of extinction and should be conserved, and propagated for commercial. Therefore, the aim of this research was to identify a suitable VW medium supplemented with organic additives for the micropropagation of D. cruentum through asymbiotic seed germination. The VW media supplemented with separate organic additives (coconut water (CW) (100 mL/L), ‘Hom Thong’ banana homogenate (BH) (1000 mg/L), and potato homogenate (PH) (1000 mg/L) or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…According to De Stefano et al [39], BH at a concentration of 1% (w/v) promoted shoot and root proliferation in Epidendrum nocturnum. A recent study by Samala and Thipwong [22] also demonstrated that BH yielded the highest number of in vitro D. cruentum plantlets. Notably, the excess of some substances in BH, specifically sugars or some trace elements, such as calcium or sodium, may inhibit cell growth and development.…”
Section: Effect Of Organic Additives On Shoot Proliferationmentioning
confidence: 82%
See 2 more Smart Citations
“…According to De Stefano et al [39], BH at a concentration of 1% (w/v) promoted shoot and root proliferation in Epidendrum nocturnum. A recent study by Samala and Thipwong [22] also demonstrated that BH yielded the highest number of in vitro D. cruentum plantlets. Notably, the excess of some substances in BH, specifically sugars or some trace elements, such as calcium or sodium, may inhibit cell growth and development.…”
Section: Effect Of Organic Additives On Shoot Proliferationmentioning
confidence: 82%
“…Apart from natural sources of carbon, mainly sugars, CW also contains some vitamins (thiamin, pyridoxine, ascorbic acid), amino acids, minerals (phosphorus, magnesium, potassium, calcium, iron, and manganese), and PGRs, such as cytokinins, zeatin, auxins (indoleacetic acid, IAA), gibberellic acid (GA), and abscisic acid (ABA), which are essential for plant cell division, differentiation, and development [18,20,24,26,27]. CW has been successfully used to promote shoot proliferation in several plants, such as Musa acuminata [24], Dendrobium chryseum [28], Dianthus caryophyllus [29], Hylocereus polyrhizus [30], Coelogyne pandurata [21], Echinacea purpurea [31], Cymbidium aloifolium [32], and D. cruentum [22]. According to DMRT analysis, means followed by distinct letters within a column are significantly different at p ≤ 0.05.…”
Section: Effect Of Organic Additives On Shoot Proliferationmentioning
confidence: 99%
See 1 more Smart Citation